Survival probabilities of thornback skate (Raja clavata) and spotted skate (Raja montagui) discarded by tickler chain beam trawl, pulse trawl, and flyshoot fisheries. - Edward Schram; Lennert van de Pol; Katinka Bleeker; Pieke Molenaar; Allard van Mens; Jan Jaap Poos; Karolina Molla Gazi; Suzanne Cornelisse; Pim van Dalen; Wouter Suykerbuyk; Jurgen Batsleer (PLoS ONE)
We measured discards survival probabilities of thornback (Raja clavata) and spotted skate (Raja montagui) in tickler chain beam trawling (5 trips, n = 183 for thornback skate, n = 137 for spotted skate), pulse beam trawling (9 trips, n = 94 for thornback skate) and flyshoot fishieres (4 trips, n = 137 for thornback skate, n = 24 for spotted skate). Survival probabilities were measured by captive observation for 15 to 25 days post catch. All fishery operations were conducted in the southern North Sea (ICES division 27.4.c) and in the Eastern English Channel (ICES division 27.7.d) according to the regular commercial practices of the fishing vessels. Trips were spread out over the seasons to account for the effect of variable environmental and fishing conditions on discards survival. Operational and environmental conditions during sea trips were recorded. For beam trawling survival probabilities (95% CI) were 50% (43-57) for thornback and 44% (37-54) for spotted skate. For pulse trawling, survival probability of thornback skate was 54% (40-65). For flyshooting survival probabilities were higher: 80% (73-87) for thornback and 75% (60-94) for spotted skate. Survival probabilities were significantly affected by gear, catch processing time, water temperature, wave height and the interaction between water temperature and wave height. We found no evidence for effects of species and length on survival probability. Vitality class provides a useful qualitative prediction of survival probability within gear. These findings are relevant for the fisheries management of skates stocks in the North Sea and English Channel.